Zenius Stimulation during a Pandemic: Framing of Republika.co.id and Liputan6.com on Distance Learning Issues in the Pandemic Era - Natasia Angreani; Rustono Farady Marta; Rama Kertamukti; Miranda Millian Kartono; Phang Kerry Cong (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
Indonesiaâ€™s education sector has also been affected by the Covid-19 pandemic. The learning process has changed from conventional to online learning. Many students find it challenging to capture and understand their knowledge because they are accustomed to the learning process through face-to-face interactions with teachers. Teachers need to create a teaching system that is more efficient than just completing the curriculum. Regarding this problem, Zenius, as an educational application from Indonesia, issued the â€œZenius Untuk Guruâ€ platform, which helps teachers create learning systems. The product launch attracted influential online media in Indonesia, Liputan6.com and Republika.co.id. The interesting point about the launch platform is that these two online media display the related news with different framing. This research using Entmanâ€™s framing theory to describe how the two media perceive the platform. The results show that Liputan6. com frames Zenius commercially, while Republika.co.id communicates Zenius as a problem solver to improve teacher literacy in less technologically literate areas. Zenius also helps Indonesia in equalizing education to remote areas of Indonesia.